2013
DOI: 10.17129/botsci.428
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth and urease activity of Helicobacter pylori by Korean edible seaweed extracts

Abstract: Abstract:Of 27 Korean seaweed species screened for potential anti-H. pylori activity, seven (25.9%) showed strong inhibitory activity based on the agar diffusion method. The strongest activity was observed for ethanol extracts from Ishige okamurae. At 1 mg/disk, the inhibition zone of I. okamurae extract was 9.0 mm, and the minimum inhibitory concentration was 12 μg/ml based on the broth microdilution assay. Based on the free urease assay system, the 80% methanol extracts from I. okamurae had 75.4% inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies have reported the anti‐inflammatory, antitumor, and anti‐aging properties of PY (Ha et al, 2020 ; Lee et al, 2014 ; Lee, Kim, Choi, et al, 2015 ; Lee, Kim, & Nam, 2015 ; Park et al, 2015 ; Wang et al, 2020 ). Another red alga, MP, exhibits antimicrobial and B cell‐stimulating activities (Lee et al, 2013 , 2021 ; Liu et al, 1997 ). Anthocyanin is one of the unique components of MP, in addition to a substantial concentration of phenolic compounds and flavonoids (Shin et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the anti‐inflammatory, antitumor, and anti‐aging properties of PY (Ha et al, 2020 ; Lee et al, 2014 ; Lee, Kim, Choi, et al, 2015 ; Lee, Kim, & Nam, 2015 ; Park et al, 2015 ; Wang et al, 2020 ). Another red alga, MP, exhibits antimicrobial and B cell‐stimulating activities (Lee et al, 2013 , 2021 ; Liu et al, 1997 ). Anthocyanin is one of the unique components of MP, in addition to a substantial concentration of phenolic compounds and flavonoids (Shin et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%